2013
DOI: 10.1242/dev.088583
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E controlsDrosophilafemale germline stem cell maintenance independently of its role in proliferation by modulating responsiveness to niche signals

Abstract: SUMMARYStem cells must proliferate while maintaining 'stemness'; however, much remains to be learned about how factors that control the division of stem cells influence their identity. Multiple stem cell types display cell cycles with short G1 phases, thought to minimize susceptibility to differentiation factors. Drosophila female germline stem cells (GSCs) have short G1 and long G2 phases, and dietdependent systemic factors often modulate G2. We previously observed that Cyclin E (CycE), a known G1/S regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 76 publications
9
88
1
Order By: Relevance
“…In contrast to regulation of cycling of invertebrate C. elegans and Drosophila premeiotic GSCs, where a G1 is nearly absent and Cyclin E is expressed throughout the cycle, 18,21 we show that O. dioica, pre-meiotic, germline nuclei have a G1-phase. During the period of syncytial germline nuclear proliferation, both the Cyclin Db and Dd variants are expressed.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In contrast to regulation of cycling of invertebrate C. elegans and Drosophila premeiotic GSCs, where a G1 is nearly absent and Cyclin E is expressed throughout the cycle, 18,21 we show that O. dioica, pre-meiotic, germline nuclei have a G1-phase. During the period of syncytial germline nuclear proliferation, both the Cyclin Db and Dd variants are expressed.…”
Section: Discussioncontrasting
confidence: 83%
“…18,19,21 The O. dioica Cyclin D variants, Da, Db, Dc and Dd are encoded by 4 different genes. 24 Previously, we have shown that O. dioica Cyclin Dd regulates G1-phase in mitotically proliferating cells during early development and in post-metamorphic somatic endocycling cells.…”
Section: Asynchronously Proliferating O Dioica Germ Nuclei Have a DImentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the three B-type cyclins work in specific ways to maintain the balance between GSC self-renewal and differentiation. The G1/S cyclin E is also essential for the maintenance of female GSCs (18). Taken together, these data show that the levels of CycA and several other cyclins are critical to ensure the proper balance between self-renewal and differentiation in stem cells.…”
mentioning
confidence: 68%
“…Because cells are more responsive to extracellular cues in G1, a short G1 would favor selfrenewal by shortening the time window during which stem cells can respond to differentiation signals. In Drosophila female GSCs, the G1 phase is also short and most of the cell cycle is spent in G2 (18). In addition, recent work in human embryonic stem cells shows that the maintenance of their pluripotency is actively controlled in S and G2 phases, through the ATM and Cyclin B1 pathways (20).…”
mentioning
confidence: 99%